Penggunaan Model Pembelajaran Problem Based Learning dalam Peningkatan Hasil Belajar Matematika pada Materi Pengukuran Siswa Kelas IIA SD Negeri Pondok 02 (Lembaga Pengembangan Kinerja Dosen, 2025)
Teachers play an important role in choosing the right learning model, which is closely related to student learning outcomes. This is still not in accordance with the practice in the field where the understanding is only temporary, so that the level of student learning in solving mathematical problems is still low. The purpose of this study is to improve students' mathematics learning outcomes using the Problem Based Learning (PBL) learning model. Class IIA students of Pondok 02 Elementary School totaling 19 students were the subjects of this study. The object of this study is an effort to improve mathematics learning outcomes in measurement material using the Problem Based Learning model. The research method uses Classroom Action Research which is carried out in three cycles. In collecting data using observation techniques and tests in the form of formative test results at the end of each cycle. For data analysis using simple statistics. The results of the study showed that the use of the Problem Based Learning (PBL) model can improve students' mathematics learning outcomes as evidenced by the increase in the percentage of students who achieve the learning completeness criteria from the initial condition (pre-cycle) which is 52.63% to 53% in cycle I, then in cycle II reaching 84%, and in cycle III the percentage reaches 95%. Thus, it is concluded that the use of the Problem Based Learning (PBL) model can improve mathematics learning outcomes in the measurement material of class IIA SD Negeri Pondok 02.